Gene Expression Reaction Norms Unravel the Molecular and Cellular Processes Underpinning the Plastic Phenotypes of Alternanthera Philoxeroides in Contrasting Hydrological Conditions - Gao, Lexuan; Geng, Yupeng; Yang, Hongxing; Hu, Yonghong; Yang, Ji (Frontiers in Plant Science, 2015)
Alternanthera philoxeroides is an amphibious invasive weed that can colonize both aquatic and terrestrial habitats. Individuals growing in different habitats exhibit extensive phenotypic variation but little genetic differentiation. Little is known about the molecular basis underlying environment-induced phenotypic changes. Variation in transcript abundance in A. philoxeroides was characterized throughout the time-courses of pond and upland treatments using RNA-Sequencing. 7,805 genes demonstrated variable expression in response to different treatments，forming 11 transcriptionally coordinated gene groups. Functional enrichment analysis of plastically expressed genes revealed pathway changes in hormone-mediated signaling, osmotic adjustment, cell wall remodeling and programmed cell death, providing a mechanistic understanding of the biological processes underlying the phenotypic changes in A. philoxeroides. Both transcriptional modulation of environmentally sensitive loci and environmentally dependent control of regulatory loci influenced the plastic responses to the environment. Phenotypic responses and gene expression patterns to contrasting hydrological conditions were compared between A. philoxeroides and its alien congener A. pungens. The terricolous A. pungens displayed limited phenotypic plasticity to different treatments. It was postulated based on gene expression comparison that the interspecific variation in plasticity between A. philoxeroides and A. pungens was not due to environmentally-mediated changes in hormone levels but to variations in the type and relative abundance of different signal transducers and receptors expressed in the target tissue.